Similar efficacy and tolerability of double-dose chloroquine and artemether-lumefantrine for treatment of Plasmodium falciparum infection in Guinea-Bissau: a randomized trial. - Ursing, J; Kofoed, P; Rodrigues, A; Blessborn, D; Thoft-Nielsen, R; Björkman, A; Rombo, L (2011)
BACKGROUND: In 2008, Guinea-Bissau introduced artemether-lumefantrine for treatment of uncomplicated malaria. Previously, 3 times the standard dose of chloroquine, that was probably efficacious against Plasmodium falciparum with the resistance-associated chloroquine-resistance transporter (pfcrt) 76T allele, was routinely used. The present study compared the efficacy and tolerability of a double standard dose of chloroquine with the efficacy and tolerability of artemether-lumefantrine. METHODS: In a randomized open-label clinical trial, artemether-lumefantrine or chloroquine (50 mg/kg) were given as 6 divided doses over 3 days to children aged 6 months--15 years who had uncomplicated P. falciparum monoinfection. Drug concentrations were measured on day 7. P. falciparum multidrug resistance gene N86Y and pfcrt K76T alleles were identified. RESULTS: The polymerase chain reaction-adjusted day 28 and 42 treatment efficacies were 162 (97%) of 168 and 155 (97%) of 161, respectively, for artemether-lumefantrine and 150 (95%) of 158 and 138 (94%) of 148, respectively, for chloroquine. When parasites with resistance-associated pfcrt 76T were treated, the day 28 efficacy of chloroquine was 87%. No severe drug-related adverse events were detected. Symptom resolution was similar with both treatments. CONCLUSIONS: Both treatments achieved the World Health Organization-recommended efficacy for antimalarials that will be adopted as policy. High-dose chloroquine treatment regimes should be further evaluated with the aim of assessing chloroquine as a potential partner drug to artemisinin derivatives. Clinical trials registration. NCT00426439.